Sprachen, Völker und Phantome. Sprach- und kulturwissenschaftliche Studien zur Ethnizität - Mumm, Peter-Arnold (Münchner Vorlesungen zu Antiken Welten, 2018)
Academics have long stopped speaking of "peoples" and "their" languages and cultures. Yet languages and cultures are still taken as evidence of quasi-ethnic community and "identity." Nine papers by scholars in Egyptology, general linguists, archeology, German-Romance onomastics, Hittite studies, and Turkish studies reveal the incongruities between linguistic community, ethnicity, and culture.